SISTEM PENGOLAHAN DATA UJIAN DI BIRO ADMINISTRASI AKADEMIK UNIVERSITAS SAHID SURAKARTA - Dhamayanti, Irma; Retnoningsih, Dwi; Anwariningsih, Sri Huning (JURNAL GAUNG INFORMATIKA, 2016)
The Directorate of Academic University Sahid of Surakarta as academic data  processing center has a very important role in supporting all the academic activities. During this time there were frequent difficulties for officials from the Directorate of  Academic Sahid University of Surakarta in the service process especially if the test data  to be processed is quite numerous and complex. This system is built using PHP and  MySQL as the database This system is expected to be a facility that supports the service process Sahid  exams at the University of Surakarta. Software development methods using waterfall  method. The purpose of this final project is to produce a Service System Exam Sahid  University of Surakarta. Thissystem contains data study program, the data curricula,  the data lecturers, distribution data subjects, the student data, the data space, the data  KRS, and data supervisor, the exam schedule, the test card, recaps invigilator, reports  exam schedules and recap reports invigilator, Testing is done by using black box  testing.